Solid sampling: advantages and challenges for chemical element determination-a critical review - Machado, Raquel C; Andrade, Daniel F; Babos, Diego V; Castro, Jeyne P; Costa, Vinicius C; Sperança, Marco Aurelio; Garcia, José Augusto; Gamela, Raimundo R; Pereira-Filho, Edenir R (Journal of analytical atomic spectrometry, 2020)
In recent decades, direct solid sample analysis has been reported in the literature as an alternative to traditional methods of sample preparation, becoming well established in the atomic spectrometry field. Therefore, this review discusses recent advances in different techniques such as flame atomic absorption spectrometry, graphite furnace atomic absorption spectrometry, high-resolution continuum source graphite furnace atomic absorption spectrometry, electrothermal vaporization, laser ablation, laser-induced breakdown spectroscopy, X-ray fluorescence spectrometry, glow discharge optical emission and mass spectrometry and arc/spark optical emission spectrometry, which are the most commonly used techniques for solid sample analysis. New possibilities such as nonmetal detection through molecular emission or absorption signals, speciation analysis, portable instrumentation for in situ analysis, and surface elemental mapping for obtaining chemical imaging will be discussed. Aspects associated with advantages and limitations are presented, relating the main instrumental advances to the expansion of the methods developed in this subject, pointing out the potential ability to overcome spectral interference and matrix effects through the development of calibration strategies to achieve the success of solid sampling in several application areas. In recent decades, direct solid sample analysis has been reported in the literature as an alternative to traditional methods of sample preparation, becoming well established in the atomic spectrometry field.